2018
DOI: 10.3892/mmr.2018.9102
|View full text |Cite
|
Sign up to set email alerts
|

B7‑H1‑mediated immunosuppressive properties in human mesenchymal stem cells are mediated by STAT‑1 and not PI3K/Akt signaling

Abstract: Mesenchymal stem cells (MSCs), derived from either bone marrow (BM) or Wharton's jelly (WJ), inhibit the proliferation of activated T cells, and interferon (IFN)‑γ serves an important role in this process. This process is B7‑homolog (H)1‑dependent during cell contact inhibition. However, the signaling pathway involved in B7‑H1 expression in MSCs remains largely undefined. The present study demonstrated activation of B7‑H1 by engaging signal transducer and activator of transcription (STAT)‑1 signaling in MSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…34,[46][47][48][49] B7-H1 also has been shown to have considerable importance for the immunosuppressive properties of BMSCs and WJMSCs. 50 Here, we identified that B7-H1 transcriptional and translational properties were expressed to a higher degree on GMSCs compared with control cells, and especially higher on a specific GMSC cluster. Moreover, after separating GMSCs into B7-H1 high and B7-H1 low expressed subsets, we discovered that B7-H1 high expressed GMSCs displayed significantly more immunosuppressive activity than B7-H1 low expressed GMSC both in vitro and in vivo in the CIA murine model.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…34,[46][47][48][49] B7-H1 also has been shown to have considerable importance for the immunosuppressive properties of BMSCs and WJMSCs. 50 Here, we identified that B7-H1 transcriptional and translational properties were expressed to a higher degree on GMSCs compared with control cells, and especially higher on a specific GMSC cluster. Moreover, after separating GMSCs into B7-H1 high and B7-H1 low expressed subsets, we discovered that B7-H1 high expressed GMSCs displayed significantly more immunosuppressive activity than B7-H1 low expressed GMSC both in vitro and in vivo in the CIA murine model.…”
Section: Discussionmentioning
confidence: 75%
“… 34 , 46 , 47 , 48 , 49 B7-H1 also has been shown to have considerable importance for the immunosuppressive properties of BMSCs and WJMSCs. 50 …”
Section: Discussionmentioning
confidence: 99%
“…S2 , Table 2 ), which can be interpreted as that new proteins had expressed on the cell surface of hMSCs following activation and acted as additional antigens. In fact, IFN-γ, used for hMSC activation in the present study, promotes the expression of several surface molecules such as HLA-ABC and HLA-DR and secretory molecules in Ad-MSCs ( 18 ), B7-H1 in UC-MSCs ( 22 ), and ICAM-1 and VCAM-1 in Ad- and UC-MSCs ( 23 ).…”
Section: Discussionmentioning
confidence: 83%
“…Our detection of FAP protein fragments in hADSCs in the present experiment suggested that the same mechanism may be present in hADSCs. Previous reports showed that STAT1 signaling is involved in interferon (IFN)-γ-induced immunosuppression in human bone marrow-derived mesenchymal stem cells [ 25 ]. In the present study, a STAT1 protein fragment was detected in hADSCs, suggesting that a similar mechanism may exist in hADSCs.…”
Section: Discussionmentioning
confidence: 99%